Temperature dependence of graphene and N-doped graphene for gas sensor applications - R. Panyathip (2018)
© Published under licence by IOP Publishing Ltd. We report the response of graphene and N-doped graphene to ethanol vapor as gas sensors with varying the concentration of ethanol and temperature of graphene. Graphene was synthesized by chemical vapor deposition on copper foils and then was transferred to a glass slide by chemical etching. N-doped graphene was produced by annealing graphene in ammonia atmosphere. Results showed the response of both graphene and N-doped graphene are at low level up to 2.4%. The response of graphene increases with temperature up to 1.15%, but that of N-doped graphene decreases down to 0.30%. We proposed that the absorbed oxygen and nitrogen detachment are the key factors for the temperature dependence of the response of graphene and N-doped graphene, respectively.